Pengaruh Kualitas Sistem TikTok Shop terhadap Kepuasan Pelanggan Dalam Pembelian Produk Fashion Online - Novi Fitria; Syifa Laili Nurkasih; Nadiya Daniella Aulia (OKTAL : Jurnal Ilmu Komputer dan Sains, 2026)
This study aims to analyze the effect of TikTok Shop system quality on customer satisfaction in online fashion product purchases. System quality in social commerce platforms plays an important role in creating a convenient, secure, and efficient shopping experience. This research uses a quantitative approach with a survey method. Data were collected through an online questionnaire distributed to 58 TikTok Shop users in Indonesia who had purchased fashion products. Data analysis was conducted using descriptive and inferential statistical methods with SPSS version 26. The system quality variable was measured through ease of use, application interface, system stability, processing speed, and transaction security, while customer satisfaction was measured through satisfaction level, expectation fulfillment, shopping experience, repurchase intention, and recommendation willingness. The results indicate that TikTok Shop system quality has a positive and significant effect on customer satisfaction in online fashion purchases.